Relationship of Hypertension to Coronary Atherosclerosis and Cardiac Events in Patients With Coronary Computed Tomographic Angiography. Issue 2 (August 2017) - Nakanishi, Rine; Baskaran, Lohendran; Gransar, Heidi; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; Chow, Benjamin J.W.; DeLago, Augustin; et al.
Abstract : Hypertension is an atherosclerosis factor and is associated with cardiovascular risk. We investigated the relationship between hypertension and the presence, extent, and severity of coronary atherosclerosis in coronary computed tomographic angiography and cardiac events risk. Of 17 181 patients enrolled in the CONFIRM registry (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry) who underwent ≥64-detector row coronary computed tomographic angiography, we identified 14 803 patients without known coronary artery disease. Of these, 1434 hypertensive patients were matched to 1434 patients without hypertension. Major adverse cardiac events risk of hypertension and non-hypertensive patients was evaluated with Cox proportional hazards models. The prognostic associations between hypertension and no-hypertension with increasing degree of coronary stenosis severity (nonobstructive or obstructive ≥50%) and extent of coronary artery disease (segment involvement score of 1–5, >5) was also assessed. Hypertension patients less commonly had no coronary atherosclerosis and more commonly had nonobstructive and 1-, 2-, and 3-vessel disease than the no-hypertension group. During a mean follow-up of 5.2±1.2 years, 180 patients experienced cardiac events, with 104 (2.0%) occurring in the hypertension group and 76 (1.5%) occurring in the no-hypertension group (hazard ratios, 1.4; 95% confidence intervals, 1.0–1.9). Compared with no-hypertension patients without coronary atherosclerosis, hypertension patients with no coronary atherosclerosis and obstructive coronary disease tended to have higher risk of cardiac events. Similar trends were observed with respect to extent of coronary artery disease. Compared with no-hypertension patients, hypertensive patients have increased presence, extent, and severity of coronary atherosclerosis and tend to have an increase in major adverse cardiac events.